The prevalence of neck pain and its association with studying device usage and posture among students at the University of Jordan: A cross-sectional study - Mohammad Ahmad Al-Shalalfeh; Yazan Zayat; Malak Abu Al Haj; Omar Nached; Mohammad Suleiman; Ahmad Alaudat; Ahmed Salman (PLoS ONE, 2026)
Background Neck pain is one of the leading causes of discomfort and disability, especially among students who use digital devices and books for studying. This study investigates the prevalence of neck pain among students of the University of Jordan and the association of potential risk factors, including posture and study devices. Methods This cross-sectional survey was conducted at the University of Jordan. Data were collected through structured, face-to-face interviews from eligible students stratified across the University’s 20 faculties to ensure proportional representation. Known musculoskeletal disease, congenital anomalies, or prior neck/shoulder trauma or surgery cases were excluded. The questionnaire covered demographics, study behaviors, primary and secondary study utilities, posture, study duration, physical activity, and pain intensity reported based on NRS-11 scoring. Analysis was performed using JASP. We used univariate and multivariate logistic regression. Results The data analyzed showed that out of the 507 students, (52.4%) complained of neck pain within the last week, with the most complained site of pain being the neck (56%), and the least being the left shoulder (5.2%). Sitting slouched was associated with approximately two-fold higher odds of reporting neck pain compared to sitting upright with full back support (OR = 2.18, CI [1.18, 4.04], p = 0.013). Using laptops (OR = 2.65, CI [1.45, 4.87], p = 0.002) or tablets (OR = 2.68, CI [1.34, 5.36], p = 0.005) for studying was associated with a nearly 2.7-fold increase in the odds of neck pain compared with using phones. In contrast, studying with books was not significantly associated with neck pain. Conclusion Slouched sitting and use of laptops or tablets were associated with higher odds of reporting neck pain, while studying primarily on phones was associated with lower odds of reporting neck pain compared with laptops and tablets. This study identified the urgent need for ergonomic education and interventions to promote healthier study habits and reduce musculoskeletal strain in students.